A low burden of severe illness: the COVID-19 Omicron outbreak in the remote Torres and Cape region of Far North Queensland - Taunton, Caroline; Hawthorn, Leanne; Matysek, Rittia; Coates, Marlow; Pickering, Emma; Neville, Johanna; Hanson, Josh; Smith, Simon; Hempenstall, Allison (Communicable Diseases Intelligence, 2023)
A coronavirus disease 2019 (COVID-19) outbreak was declared in the remote Torres and Cape region of Far North Queensland soon after the Queensland border opened for quarantine-free domestic travel in December 2021, with a total of 7,784 cases notified during the first ten-month outbreak period. We report a crude attack rate among residents of 25.6% (95% confidence interval [95% CI]: 25.1–26.1%), a hospitalisation rate of 1.6% (95% CI: 1.3–1.9%) and a crude case fatality rate of 0.05% (95% CI: 0.01–0.13%). Hospitalisation and case fatality rates were similar among First Nations and non-Indigenous people, with double dose COVID-19 vaccination rates higher among First Nations than non-Indigenous people by the end of the outbreak period. We attribute the low burden of severe illness to local community leadership, community engagement, vaccination coverage and recency, and community participation in a local culturally considered COVID-19 care-in-the-home program.